Impact of Bilingual Support on English Language Learning among Special Students in Multilingual Classrooms in Pakistan - Sohail, Muhammad; Ul Ain, Noor; Shahzad, Waheed (JELLL, 2025)
This study explores the impact of bilingual support on English language learning among special students in multilingual classrooms in Pakistan, focusing particularly on learners with learning disabilities, hearing impairments, and mild cognitive challenges. Utilizing mixed methods, including questionnaires and semi-structured interviews with teachers and students from government and private schools in South Punjab, the research investigates the effectiveness of bilingual instructional strategies such as translanguaging and code-switching. The findings highlight significant cognitive and academic benefits of bilingual support, reinforcing sociocultural and Universal Design for Learning (UDL) theories. However, challenges related to teacher preparedness, resource limitations, and policy implementation were also identified. The study recommends enhanced teacher training, development of bilingual resources, and policy reforms to foster inclusive education for special students in Pakistan’s linguistically diverse classrooms. This research contributes to filling the gap in bilingual education literature for special needs students and offers practical implications for educators, curriculum designers, and policymakers.